TINJAUAN HUKUM PERLINDUNGAN TERHADAP PEKERJA RUMAH TANGGA - Sitti Magfirah Makmur; Irwansyah Reza Mohamad (At-Tanwir Law Review, 2021)
(Legal Protection Analysis Against Housekeepers). Under the Constitution, article 27 para 2 UUD 1945 confirms that each citizen is entitled to a decent work and livelihood. But in fact there are many cases of violence against groups of domestic workers. Although in international law has been governed by its protection system through the ILO convention, it remains a very weak position if it is not strengthened by the legal protections system of each country. This research aims to analyse the current employment legal system in Indonesia in providing legal protection against domestic helper.  The method of approach used is the normative and descriptive juridical approach. This research uses secondary data obtained from primary and secondary legal materials. The results showed that the laws and regulations of the employment sector governed by Law No. 13 of 2003 concerning employment did not reach the domestic helper group. While the Minister of Manpower Regulation No. 2 of 2015 on protection for domestic workers is still too weak because it has not been able to provide assurance of legal position and protection for domestic workers, whether in the system of wages, occupational safety, occupational health or social security programs. To ensure the position and protection of household workers must reconstruct or revise all rules pertaining to employment in order to be equality between the household worker and other workers so as to authorize the Industrial relations Court to adjudicate disputes with his employer.